Edward Hyams: Ecology and Politics 'Under the Vine'. (1st February 2011) - Smith, Mick
Abstract : This paper offers an assessment of the agricultural eco-politics of Edward Hyams (1910-75), novelist, gardener, historian, broadcaster and anarchist. It focuses in particular on his collaboration with the conservative writer on rural England, and founding member of the Soil Association, H.J. Massingham which resulted in a book, Prophecy of Famine (1953) - a fundamental critique of the effects of industrial capitalism on farming and a call for agricultural self-sufficiency and soil conservation. This collaboration between two writers with very different political views raises important questions about the nature of eco-politics and whether its critique of the dominant ideology of 'progress' (at least in its historicist forms) can still constitute a radical 'progressive' politics. Hyams' writings, and his differences from Massingham, particularly over the issue of private ownership of land, are illustrative of this apparent tension.